2021
DOI: 10.33448/rsd-v10i1.12043
|View full text |Cite
|
Sign up to set email alerts
|

Impactos globais da infecção por COVID-19 em pacientes com a doença de Parkinson: uma revisão integrativa

Abstract: O surto pandêmico de infecção pelo Coronavírus 2019-nCoV (COVID-19) é alvo pesquisas para compreender suas repercussões em pacientes com doenças neurológicas, como a doença de Parkinson. Este artigo visa discutir as evidências na literatura científica sobre os riscos e complicações da pandemia por COVID-19 sobre portadores de Parkinson. Foram realizadas buscas de artigos em inglês, português ou espanhol por meio das bases de dados PubMed, PubMed, Lilacs, ScienceDirect e SciElo, usando os descritores de forma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
1
0
0
1
Order By: Relevance
“…It was also noted that during the COVID pandemic, 54.5% of the participants adhered to total social isolation, corroborating Paiva et al [20] who concluded that the COVID-19 pandemic negatively impacted social aspects, as well as impaired the accessibility to medical centers with interruption of face-to-face visits, due to the preventive actions carried out given the high transmissibility of the SARS-CoV-2 virus, which contributed to aggravating motor and non-motor symptoms of PD. It is noteworthy that 87.9% of the individuals evaluated in this study did not receive government financial emergency aid, and financial issues can have made it difficult to obtain regular medication for PD during the period [21].…”
Section: Discussionsupporting
confidence: 81%
“…It was also noted that during the COVID pandemic, 54.5% of the participants adhered to total social isolation, corroborating Paiva et al [20] who concluded that the COVID-19 pandemic negatively impacted social aspects, as well as impaired the accessibility to medical centers with interruption of face-to-face visits, due to the preventive actions carried out given the high transmissibility of the SARS-CoV-2 virus, which contributed to aggravating motor and non-motor symptoms of PD. It is noteworthy that 87.9% of the individuals evaluated in this study did not receive government financial emergency aid, and financial issues can have made it difficult to obtain regular medication for PD during the period [21].…”
Section: Discussionsupporting
confidence: 81%
“…Atualmente, em meio à pandemia do Covid-19 aumenta-se a preocupação com a assistência à saúde dos pacientes vulneráveis, dentre eles o portador de parkinson, principalmente quanto as alterações e mentais relatadas por familiares (PAIVA et al, 2021).…”
Section: Resultsunclassified
“…2020. movement disorders. This is, presumably, a concern faced by family members and health professionals in the context of a pandemic 22 .…”
Section: Discussionmentioning
confidence: 99%